To learn, to remember, to forget—How smart is the gut?. (5th June 2019) - Schemann, Michael; Frieling, Thomas; Enck, Paul
Abstract: The enteric nervous system (ENS) resides within the gut wall and autonomously controls gut functions through coordinated activation of sensory, inter and motor neurons. Its activity is modulated by the enteric immune and endocrine system as well as by afferent and efferent nerves of the parasympathetic and sympathetic nervous system. The ENS is often referred to as the second brain and hence is able to perform sophisticated tasks. We review the evidence that the "smartness" of the ENS may even extend to its ability to learn and to memorize. Examples for habituation, sensitization, conditioned behaviour and long‐term facilitation are evidence for various forms of implicit learning. Moreover, we discuss how this may change not only basic Neurogastroenterology but also our understanding of development of gut diseases and chronic disorders in gut functions. At the same time, we identify open questions and future challenges to confirm learning, memory and memory deficits in the gut. Despite some remaining experimental challenges, we are convinced that the gut is able to learn and are tempted to answer the question with: Yes, the gut is smart.